2009
DOI: 10.1016/j.seizure.2008.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Inter-observer variability of the EEG diagnosis of seizures in comatose patients

Abstract: The EEG diagnosis of (non-convulsive) seizures in ICU patients is not very reliable, even when strict criteria such as proposed by Young are applied. There is a need for less ambiguous EEG criteria for (non-convulsive) seizures and status epilepticus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 26 publications
2
54
1
Order By: Relevance
“…However, the optimal method for describing recurrent seizures has not been established and it remains unclear whether recurrent seizures have the same impact as a single prolonged seizure. Additionally, variability is reported among neurophysiologists detecting seizures 19,20 and rhythmic or periodic patterns 21 in critically ill patients. While EEG tracings in this study were interpreted by a single pediatric neurophysiologist to improve standardization, this may impact generalization of these data.…”
Section: Results Subject and Enrollment Characteristicsmentioning
confidence: 99%
“…However, the optimal method for describing recurrent seizures has not been established and it remains unclear whether recurrent seizures have the same impact as a single prolonged seizure. Additionally, variability is reported among neurophysiologists detecting seizures 19,20 and rhythmic or periodic patterns 21 in critically ill patients. While EEG tracings in this study were interpreted by a single pediatric neurophysiologist to improve standardization, this may impact generalization of these data.…”
Section: Results Subject and Enrollment Characteristicsmentioning
confidence: 99%
“…A study of inter-observer agreement in seizure detection in critically ill adults demonstrated moderate agreement was demonstrated for seizure occurrence, but agreement was lower for more subtle seizure descriptors including their frequency, onset, and offset. (42) Similarly, identification of seizures has been shown to be very good among neonates with hypoxic-ischemic brain injury(43) and substantial among critically ill adults. (30)…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, like interictal epileptiform discharges, although there are published criteria of EEG signal characteristics for recognizing electrographic seizures and PDs, it is not rare that inter-rater agreement (IRA) among EEG experts can be very poor, especially for cases with equivocal patterns or with more complex and abnormal background activities (Ronner et al, 2009). Since IRA reliability in recognizing these critical EEG events has significant implications for the value of EEG as a diagnostic tool, it is important to design studies that are similar to the clinical practice to assess IRA.…”
Section: Introductionmentioning
confidence: 99%